Case study of shark fishing which requires more serious attention to the possibility of its sustainability as a top trophic level organism in aquatic ecosystems - Zainuri, Muhammad; Azzahir, Irsyad Maulana; Dhiyaulhaq, Khaizuran Maziz (Edelweiss Applied Science and Technology, 2025)
The purpose of this study was to determine the number, species, distribution of body length, and sex ratio. Data were collected from the Fish Production Statistics Report at the Muncar-Banyuwangi Coastal Fishing Port (2008-2022) and the Fish Production Report in Lamongan Regency (2019-2023), as well as sampling data from December 2022 to January 2023 and January to February 2024 at the Brondong Nusantara Fishing Port, Lamongan. The data were analyzed descriptively and quantitatively. The results of the study showed that shark production fluctuated and reached around 1,000 tons per year. The results of data analysis based on sampling showed that there were eight species of sharks caught, four species or 50% of which were protected sharks and listed in the Appendix (CITES II), namely the Hiu Martil (Sphyrna lewini), Hiu Lanjaman (Carcharhinus dusumieri), Hiu Karang Sirip Hitam (Carcharhinus melanopterus), and Hiu Tikus (Alopias pelagicus). Even the Hiu Martil is classified as critically endangered (CR). While other species of sharks are classified as Near Threatened (NTT). Based on their body length, most of the catches are still classified as immature. The sex ratio is known to be close to 1 (male) to 1 (female). Considering the sustainability of sharks and that some of the species caught are classified as protected by law, shark management in Indonesia should be taken more seriously to gain attention.